Data for: The influences of the AMO and NAO on the sedimentary infill in an Azores Archipelago lake since ca. 1350 AD - Hernandez, A (via Mendeley Data) (2017)
DataWe present new geochemical data of the sedimentary record of Lake Empadadas (Azores Archipelago). The Azores Archipelago, located in the North Atlantic Ocean (37°- 40° N, 25°- 31° W), comprises nine islands. At the western part of São Miguel Island, Lake Empadadas (37°49’ N - 25°45’ W) occupies the bottom of a small crater that is 740 m above sea level. Its maximum length and width are 250 m and 85 m, respectively, and its maximum water depth is 5.3 m. The total area of the lake is 0.02 km2, its total water volume is 3.7x104 m3, and the total area of the catchment is 0.10 km2. The elemental and mineralogical composition of Lake Empadadas sediments are determined using X-ray fluorescence, X-ray diffraction, Total Carbon and Nitrogen content of bulk organic matter and a quantification of the amorphous fraction of the sediments. See 'The influences of the AMO and NAO on the sedimentary infill in an Azores Archipelago lake since ca. 1350 AD' by Hernández et al. in Global and Planetary Change, for further details. THIS DATASET IS ARCHIVED AT DANS/EASY, BUT NOT ACCESSIBLE HERE. TO VIEW A LIST OF FILES AND ACCESS THE FILES IN THIS DATASET CLICK ON THE DOI-LINK ABOVE